Credit Conditions and Foreign Direct Investment During the Global Financial Crisis - Desbordes, Rodolphe; Wei, Shang-Jin (World Bank Group, Washington, DC, 2014)
This paper investigates the effect that tight credit conditions had on outward foreign direct investment flows during the 2008-2010 global financial crisis. A difference-in-differences approach is used to isolate a "credit channel" impact of the global financial crisis on foreign direct investment. The global financial crisis had a stronger negative impact on the relative volume of outward foreign direct investment in financially vulnerable sectors in more financially developed countries, especially if these countries also experienced a banking crisis. These results suggest that lack of access to external finance can partly explain the drop in foreign direct investment during the global financial crisis.